CONFLICTING VISIONS OF CONNECTIVITY: EU’S AND CHINA’S INFRASTRUCTURAL AGENDAS FOR THE WESTERN BALKANS - Stekić, Nenad; Nikolić, Jovana (National interest, 2025)
This article examines the strategic engagement of the European Union and China in the Western Balkans, analyzing their respective approaches through the EU Connectivity Agenda and China’s Belt and Road Initiative from 2015 to 2020. While both initiatives sought to enhance regional connectivity and infrastructure, they were shaped by differing agendas rooted in national interest. The EU’s approach focused on fostering economic integration and regulatory alignment with Europe, prioritizing shared standards and sustainable development. Conversely, China’s approach emphasized rapid infrastructure development as a means to expand its geopolitical influence, often leveraging state-driven investments to further its strategic interests. This study underscores how these competing agendas manifest in significant investments and their resulting impacts on regional infrastructure, economic growth, and political dynamics. The intensifying geopolitical competition between the EU and China also brings new challenges for the Western Balkan states, including debt dependency and sovereignty concerns, as they seek to balance foreign influence with national priorities. This analysis offers insight into the region’s evolving role within the broader global landscape, revealing the long-term implications of external powers pursuing both connectivity and national interests in shaping its development.